Bioaccumulation of tributyltin by blue crabs - Vannuci-silva, Monizze; Menegario, Amauri A.; Franchi, Mariana; Brossi-garcia, Ana L. [UNESP]; Souza, João M. De; Araújo Jr, Marcus A. G. De; Lopes, Monica A. F. S. Bindes G.; Govone, José S. [UNESP] (Sociedade Brasileira de Química, 2013)
This study evaluated the bioaccumulation of tributyltin (TBT) by the blue crab (Callinectes sapidus). Animals were fed with contaminated food containing 30 µg g-1 of TBT expressed as Sn. The analytes were determined in the gills, hepatopancreas and muscle. Acid digestion was used in the total Sn determination, and a solid-phase extraction technique was used for the selective determination of TBT. Limits of detection of 44.6 and 4.46 ng g-1 were found for HG-ICP OES (hydride generation-inductively coupled plasma optical emission spectroscopy) and ICP-MS (ICP-mass spectrometry), respectively. The results for non-contaminated animals were below 50 ng g-1, while the animals subjected to the contaminated food showed higher tissue concentrations of Sn (until 6229 ng g-1) and TBT (until 3357 ng g-1) related to the number of exposure days. According to the results, Sn is bioaccumulated by the blue crab in higher concentrations in the hepatopancreas. For most of these animals, the results suggest that Sn is bioaccumulated as TBT.

O presente estudo avaliou a bioacumulação de tributilestanho (TBT) pelo siri azul (Callinectes sapidus). Os animais foram alimentados com comida contaminada com 30 µg g-1 de TBT, expresso como Sn. Os analitos foram determinados nas brânquias, hepatopâncreas e músculo. Realizou-se uma digestão ácida para determinação da concentração total de Sn, e a técnica de extração em fase sólida foi utilizada para determinação seletiva de TBT. Obteve-se limites de detecção de 44,6 e 4,46 ng g-1 para HG-ICP OES (geração de hidretos (HG) por espectrometria de emissão óptica com plasma indutivamente acoplado) e ICP-MS (ICP-espectrometria de massas), respectivamente. Os resultados para os tecidos dos animais não contaminados foram inferiores a 50 ng g-1, enquanto os submetidos à alimentação contaminada mostraram elevadas concentrações de Sn (até 6229 ng g-1) e TBT (até 3357 ng g-1) relacionadas aos dias de exposição. De acordo com os resultados, Sn é acumulado pelo siri azul em elevadas concentrações no hepatopâncreas. Para a maioria dos animais, os resultados sugerem que o Sn é bioacumulado como TBT.
Keywords: tin bioaccumulation; speciation; HG-ICP OES; ICP-MS